Experiencias producidas por el confinamiento de la covid-19 en las familias del barrio Santander del municipio Maicao la guajira. (2023)
This research entitled "Behavioral Effects produced by the confinement of covid-19 in families in the Santander neighborhood of the Maicao La Guajira municipality, which is constituted in a qualitative study seeks to analyze the behavioral changes in the chosen unit of análisy, from of the psychological, family, physical and economic effects of quarantine or confinement, due to covid 19, in that sense an objective study is carried out based on the experience of the chosen sample, located in the Santander neighborhood of the Municipality of Maicao, For this, the literature or state of the art on the subject was reviewed, the category of behavioral effect was displayed through the theorization of the incidences of psychological, physical, family and economic factors, the unit of analysis was reached in order to know the behavior of the study indicators, concluding that the effects produced by the confinement of COVID 19 affected the conduct of the different members of the affected families and it is recommended, from the accompaniment of the health sector, to provide psychological assistance to people who suffer from this disease and their families, in order to minimize the negative effects produced by it.